Karl Jaspers: a portrait of a philosopher–psychiatrist - Jerotić, Stefan (Engrami, 2022)
Karl Jaspers was a philosopher and a psychiatrist. He made numerous contributions to both disciplines during his lifetime. The most significant contribution within psychiatry was the introduction of the phenomenological method and the creation of phenomenological psychopathology, which forms the basis of the psychopathological assessment. Moreover, he introduced the distinction between explanation and understanding into psychopathology, thus enriching our conceptual knowledge. By clarifying these concepts, Jaspers helped our strivings towards perceiving the patient as a person, instead of an object waiting to be analyzed. As a philosopher, a “neo-Kantian”, within his philosophy of existence he developed numerous insights, especially highlighting so-called limit-situations. Limit-situations include experiences such as: death, suffering/struggle, randomness, and guilt. Such situations touch the limit of experience and point to what is transcendental, while at the same time, opening up possibilities for the realization of one’s own authenticity. This paper highlights Jaspers’ most significant contributions and describes Jaspers’ professional development, while also describing some elements of his personality and upbringing.
Keywords: Karl Jaspers; psychopathology; phenomenology; philosophy of existence; limit situations